METHOD OF NAHWU IN ARABIC LEARNING - M. Asy'ari, M. Asy'ari (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2020)
Language is very important and the impression that Nahwu is a difficult science to learn, especially by Muslims. As one of the basic sciences in Arabic, Nahwu's science cannot be ignored because without Nahwu's knowledge, Arabic will become chaotic and the order of words and sentences will be disorganized. Therefore, in learning Arabic, it is important to know Nahwu's knowledge, even though this method of teaching science is quite widely practiced by nahwu teachers, but students continue to face difficulties in learning it. Therefore, it is necessary to use suitable teaching methods and appropriate steps and subject matter that must be prioritized to be taught to students, so as to facilitate them in learning Nahwu science. The function of the learning method is one tool to achieve the goal. By using methods accurately the teacher will be able to achieve the learning objectives. When goals are formulated so that students have certain skills, the methods used must be adapted to the goals. Language learning methods, including Arabic, have evolved over time along with the development of the underlying theories, the results of research and experimentation in language teaching, as well as the development of the demands of the community's needs in the language field.